The Impact of Thin Captialization Rules on Shareholder Financing - Maßbaum, Alexandra; Sureth-Sloane, Caren

Unternehmensbewertung für substanzsteuerliche Zwecke - Eine empirische Analyser des Stuttgarter Verfahrens und alternative Ansätze - Müller, Jens; Sureth-Sloane, Caren

Steuern und Risiko als substitutionale oder komplementäre Determinanten unternehmerischer Investitionspolitik? - Niemann, Rainer; Sureth-Sloane, Caren

Auswirkungen einer Reform des Erbschaft- und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens- und Grundvermögen - Sureth-Sloane, Caren; Müller, Jens; Houben, Henriette; Maiterth, Ralf (Untrnehmensbesteuerung 2008: Neue Wege gehen)

Kritische Anmerkungen zur Ermittlung des tatsächlichen Werts einer Familienpersonengesellschaft nach neuer Rechtslage - Sureth-Sloane, Caren; Nordhoff, Daniel (Der Betrieb)

Praxisnähe und universitäre Ausbildung: Fallstudie der Universität Paderborn - Sureth-Sloane, Caren; Nordhoff, Daniel (DATEV BILDUNGSforum)

Proposals for a European Corporate Taxation and Their Influence on Multinationals' Tax Planning - Sureth-Sloane, Caren; Üffing, Michaela

Neural networks in 3D medical scan visualization - Zukic, D.; Elsner, A.; Avdagic, Z.; Domik, Gitta (Proceedings of 11th International Conference on Computer Graphics and Artificial Intelligence)

Navigierbare Kompression von XML-Datenströmen - Hartel, Rita

Detecting Suspicious Relational Database Queries - Böttcher, Stefan; Hartel, Rita; Kirschner, Matthias (Third International Conference on Availability, Reliability and Security)

BSBC: Towards a Succinct Data Format for XML Streams - Böttcher, Stefan; Hartel, Rita; Heinzemann, Christian (WEBIST 2008, Proceedings of the Fourth International Conference on Web Information Systems and Technologies)

Compressing XML Data Streams with DAG+BSBC - Böttcher, Stefan; Hartel, Rita; Heinzemann, Christian (Web Information Systems and Technologies, 4th International Conference, WEBIST 2008, Revised Selected Papers)

Ultraschall-Messtechnik und Ultraschall-Tomografie - Henning, Bernd

Development status and market potential of hot formed ballistic steels - Tröster, Thomas; Howe, C.; Müller, M.; Rostek, W.

The Effect of Texture on the Fatigue Properties of Ultrafine-Grained Interstitial-Free Steel - Niendorf, Thomas; Marten, Thorsten; Maier, Hans J.; Karaman, Ibrahim (Materials Science Forum)
The present paper reports on the effect of texture on the cyclic stress-strain response (CSSR) and the fatigue life of ultrafine-grained (UFG) interstitial-free (IF) steel. Tests in the lowcycle fatigue (LCF) regime were conducted on material that was processed by the equal channel angular extrusion (ECAE) technique along the so called “efficient” route 8E. This route has been shown to result in a homogeneous microstructure with a high fraction of high angle grain boundaries (HAGBs), which are beneficial for a stable CSSR. In addition, the evolution of the microstructure was characterized by means of electron optical techniques, including electron backscattered diffraction, and by X-Ray diffractometry. It was found that the initial texture of specimens cut from the ECAE billet along different orientations with respect to the extrusion direction (ED) has a substantial effect on the CSSR of the UFG IF steel. Furthermore, microscopy results indicated the notable influence of the last ECAE processing step on the evolution of damage in the material.

Is an ordinal class structure useful in classifier learning? - Hühn, J.; Hüllermeier, Eyke (International Journal of Data Mining, Modeling and Management)

Label ranking by learning pairwise preferences - Hüllermeier, Eyke; Fürnkranz, J.; Cheng, W.; Brinker, K. (Artificial Intelligence)

A critical analysis of variants of the AUC - Vanderlooy, S.; Hüllermeier, Eyke (Machine Learning)

Multilabel classification via calibrated label ranking - Fürnkranz, J.; Hüllermeier, Eyke; Mencia, E.; Brinker, K. (Machine Learning)

Learning valued preference structures for solving classification problems - Hüllermeier, Eyke; Brinker, K. (Fuzzy Sets and Systems)

Case-based learning in a bipolar possibilistic framework - Beringer, J.; Hüllermeier, Eyke (International Journal of Intelligent Systems)

Granular computing in machine learning and data mining - Hüllermeier, Eyke (Handbook on Granular Computing)

Ein verfeinertes elektrisches Modell für Teilchentreffer und dessen Auswirkung auf die Bewertung der Schaltungsempfindlichkeit - Coym, Torsten; Hellebrand, Sybille; Ludwig, Stefan; Straube, Bernd; Wunderlich, Hans-Joachim; G. Zoellin, Christian
Keywords: WORKSHOP

Testen mit Rücksetzpunkten - ein Ansatz zur Verbesserung der Ausbeute bei robusten Schaltungen - Amgalan, Uranmandakh; Hachmann, Christian; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Research Note: Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Research Note—Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Multimedia Production with a Content HUB Environment. Media Engineering for Mobile Computing Courseware - Herzog, Michael A.; Trier, Matthias (2007 4th IEEE Workshop on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications)

SCORM (Shared Content Object Reference Model) - Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Workflow-Modellierung - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Systemanalyse - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Random network coding in wireless sensor networks: Energy efficiency via cross-layer approach - Platz, Daniel; Woldegebreal, Dereje H; Karl, Holger (Spread Spectrum Techniques and Applications, 2008 IEEE 10th International Symposium on)

Enabling partial forwarding by decoding-based one and two-stage selective cooperation - Valentin, Stefan; Volkhausen, Tobias; Onat, Furuzan Atay; Yanikomeroglu, Halim; Karl, Holger (Communications Workshops, 2008. ICC Workshops' 08. IEEE International Conference on)

Fuzzy methods in data mining - Hüllermeier, Eyke (Encyclopedia of Data Warehousing and Mining - Second Edition)

Relating embedding and coloring properties of snarks - Mohar, Bojan; Steffen, Eckhard; Vodopivec, Andrej (Ars Mathematica Contemporanea)

Learning preference models from data: On the problem of label ranking and its variants - Hüllermeier, Eyke; Fürnkranz, J. (Preferences and Similarities)

Supporting case-based retrieval by similarity skylines: Basic concepts and extensions - Hüllermeier, Eyke; Vladimirskiy, I.; Prados Suarez, B.; Stauch, E. (in Proceedings ECCBR-2008 9th European Conference on Case-Based Reasoning, Trier, Germany)

Learning similarity functions from qualitative feedback - Cheng, W.; Hüllermeier, Eyke (in Proceedings ECCBR-2008 9th European Conference on Case-Based Reasoning, Trier, Germany)

Realizing Reconfigurable Mesh Algorithms on Softcore Arrays - Giefers, Heiner; Platzner, Marco (Proceedings of the International Symposium on Systems, Architectures, Modeling and Simulation (SAMOS))

Communication and Synchronization in Multithreaded Reconfigurable Computing Systems - Lübbers, Enno; Platzner, Marco (Proceedings of the 8th International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

A portable abstraction layer for hardware threads - Lübbers, Enno; Platzner, Marco (Proceedings of the 18th International Conference on Field Programmable Logic and Applications (FPL))

Optical anisotropy of the In/Si(111)(4×1)/(8×2) nanowire array - Wippermann, S.; Schmidt, Wolf Gero (Surface Science)

Water adsorption on clean Ni(111) and p(2×2)-Ni(111)-O surfaces calculated from first principles - Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Spatial modulation of molecular adsorption energies due to indirect interaction - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Influence of the Side Group Aromaticity on the Organic Molecule Adsorption on Cu(110) - Rauls, E.; Schmidt, Wolf Gero (Journal of Physical Chemistry C)

Atomic structure and energetics of thec-GaN(001) surface - Rauls, E.; Dijkstra, S. J.; Schmidt, Wolf Gero (Physical Review B)

DFT calculations of adenine adsorption on coin metal (110) surfaces - Rauls, E.; Blankenburg, S.; Schmidt, Wolf Gero (Surface Science)

Resolving the Optical Spectrum of Water: Coordination and Electrostatic Effects - Hermann, A.; Schmidt, Wolf Gero; Schwerdtfeger, P. (Physical Review Letters)

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

GaN and InN conduction-band states studied by ellipsometry - Rakel, Munise; Cobet, Christoph; Esser, Norbert; Fuchs, Frank; Bechstedt, Friedhelm; Goldhahn, Rüdiger; Schmidt, Wolf Gero; Schaff, William (Physical Review B)

Adatom-Induced Conductance Modification of In Nanowires: Potential-Well Scattering and Structural Effects - Wippermann, S.; Koch, N.; Schmidt, Wolf Gero (Physical Review Letters)

Ammonia adsorption on Cl/Si(001): First-principles calculations - Lange, B.; Schmidt, Wolf Gero (Surface Science)

LiNbO3ground- and excited-state properties from first-principles calculations - Schmidt, Wolf Gero; Albrecht, M.; Wippermann, S.; Blankenburg, S.; Rauls, E.; Fuchs, F.; Rödl, C.; Furthmüller, J.; Hermann, A. (Physical Review B)

Paralleling of LLC Resonant Converters using Frequency Controlled Current Balancing - Figge, Heiko; Fröhleke, Norbert; Schafmeister, Frank; Ide, Peter (Proc. DPEC Seminar)

Semi-Digital Interleaved PFC Control - Grote, Tobias; Fröhleke, Norbert; Schafmeister, Frank; Ide, Peter (Proc. DPEC Seminar)

Matrixkonverter, Kapitel 3.8 - Kolar, Johann; Schafmeister, Frank (Lehrbuch Leistungselektronische Schaltungen,)

Control of permanent magnet synchronous motor with dual-mode position estimation - Böcker, Joachim; Kröger, Claus (2005 European Conference on Power Electronics and Applications)

Optimized size design of integrated magnetic components using area product approach - Nijende, H.; Fröhleke, N.; Böcker, Joachim (2005 European Conference on Power Electronics and Applications)

Fuel cell inverter system with integrated auxiliary supply - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ide, P.; Kunze, J. (2005 European Conference on Power Electronics and Applications)

Direct torque control for interior permanent magnet synchronous motors with respect to optimal efficiency - Meyer, Michael; Grote, Tobias; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Run-time reconfiguration of FPGA-based drive controllers - Schulz, B.; Paiz, C.; Hagemeyer, J.; Mathapati, S.; Porrmann, M.; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Construction of a hybrid electrical racing kart as a student project - Knoke, Tobias; Schneider, Tobias; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Optimal Power Train Design of a Hybrid Refuse Collector Vehicle - Knoke, Tobias; Böcker, Joachim (2007 IEEE Vehicle Power and Propulsion Conference)

Implementation of dynamically reconfigurable control structures on a single FPGA platform - Mathapati, Shashidhar; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Logik als Ethik des Denkens: Der Tübinger Philosoph Christoph Sigwart (1830-1904) und die Logik des 19. Jahrhunderts - Peckhaus, Volker (Methodisches Denken im Kontext. Festschrift für Christian Thiel. Mit einem unveröffentlichten Brief Gottlob Freges)

W. R. Hamilton (1805–1865) - Peckhaus, Volker (Handbook of Whiteheadian Process Thought)

Logic and Metaphysics: Heinrich Scholz and the Scientific World View - Peckhaus, Volker (Philosophia Mathematica)
Abstract: Zbl. Math. 1144.03003 (Reinhard Kahle).

Paralleling of LLC resonant converters using frequency controlled current balancing - Figge, H.; Grote, T.; Froehleke, N.; Boecker, J.; Ide, P. (2008 IEEE Power Electronics Specialists Conference)

LLCC-PWM inverter for driving high-power piezoelectric actuators - Li, R.; Fröhleke, N.; Böcker, Joachim (13th International Power Electronics and Motion Control Conference, Poznan, Poland)

Linear switched reluctance motor as a high efficiency propulsion system for railway vehicles - Kolomeitsev, L.; Kraynov, D.; Pakhomin, S.; Rednov, F.; Kallenbach, E.; Kireev, V.; Schneider, T.; Böcker, Joachim (2008 International Symposium on Power Electronics, Electrical Drives, Automation and Motion)

System Architecture and Risk Management for Autonomous Railway Convoys - Henke, Christian; Tichy, Matthias; Schneider, Tobias; Böcker, Joachim; Schäfer, Wilhelm (2008 2nd Annual IEEE Systems Conference)

Analysis and Design of a Novel Three-Level LLCC Inverter Supplying an Airborne Piezoelectric Brake Actuator - Li, Rongyuan; Fröhleke, Norbert; Böcker, Joachim (2007 IEEE Power Electronics Specialists Conference)

Design of Power Supply for Driving High Power Piezoelectric Actuators - Li, Rongyuan; Lönneker, Michael; Fröhleke, Norbert; Böcker, Joachim (2008 IEEE Industry Applications Society Annual Meeting)

Die Zeitschrift für die Grundlagen der gesamten Mathematik. Ein gescheitertes Zeitschriftenprojekt aus dem Jahre 1908 - Peckhaus, Volker (Publikationsstrategien einer Disziplin. Mathematik in Kaiserreich und Weimarer Republik)

Fixing Cantor’s Paradise: The Prehistory of Ernst Zermelo’s Axiomatization of Set: Theory - Peckhaus, Volker (New Approaches to Classes and Concepts)
Rezension: MR 2777837 (2012a:03003, J. Dawson).

¿Adiós Descartes? Una rehabilitación pragmática del racionalismo - Peckhaus, Volker (Filosofía y historia de la ciencia en el Cono Sur)

Anthropologismus als ‚guter Psychologismus‘, erweiterte Stellungnahme zu Christoph Sigwart, „Die Zahlbegriffe“ (1904) - Peckhaus, Volker (Erwägen, Wissen, Ethik)

Zu Christoph Sigwarts ‚Die Zahlbegriffe‘, Ausgangsstellungnahme zu Christoph Sigwart, „Die Zahlbegriffe“ (1904) - Peckhaus, Volker (Erwägen, Wissen, Ethik)

Control of a linear switched reluctance motor as a propulsion system for autonomous railway vehicles - Kolomeitsev, L.; Kraynov, D.; Pakhomin, S.; Rednov, F.; Kallenbach, E.; Kireev, V.; Schneider, T.; Böcker, Joachim (2008 13th International Power Electronics and Motion Control Conference)

Galois, Évariste - Peckhaus, Volker; v. Bülow, Christopher (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Frege, Friedrich Ludwig Gottlob - Peckhaus, Volker (New Dictionary of Scientific Biography, 8 Bde., Bd. 3: Fairey–Hypatia)

Gregory, Duncan Farquharson - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Grellingsche Antinomie - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Graßmann, Robert - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Genidentität - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Hermes, Hans - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Taking Fingerprints of Speech-And-Gesture Ensembles. Approaching Empirical Evidence of Intrapersonal Alignment in Multimodal Communication - Lücking, Andy; Mehler, Alexander; Menke, Peter (Proceedings of 12th Workshop on Semantics and Pragmatics of Dialogue)

Simon Blackburn, The Oxford Dictionary of Philosophy, second edition. Oxford: Oxford University Press, 2005 - Peckhaus, Volker (History and Philosophy of Logic)

Johann Heinrich Lambert. Philosophische Schriften. Vol. VIII: Kleinere philosophische Abhandlungen und Rezensionen. Edited by A. Emmel and A. Spree, Georg Olms Verlag, Hildesheim, Zurich and New York 2007, Part 1, Part 2 - Peckhaus, Volker (Bulletin of Symbolic Logic)

Special Issue: Leopold Löwenheim (1878-1957). Edited by C. Thiel, History and Philosophy of Logic, vol. 28, no. 4 (November 2007). Taylor & Francis, Abingdon, Oxon, UK, pp. 289–336 - Peckhaus, Volker (Bulletin of Symbolic Logic)

Grußwort des Dekans der Fakultät für Kulturwissenschaften - Peckhaus, Volker (Verabschiedung Prof. Dr. Wolfgang Keim)

VIRTEX – Lehr- und Lernmaterialien für den Fachsprachenunterricht in Hotel und Gastronomie - Ballweg, Sandra (Auf neuen Wegen. Deutsch als Fremdsprache in Forschung und Praxis. Tagungsband der 35. Jahrestagung des Fachverbandes Deutsch als Fremdsprache 2007 an der Freien Universität Berlin)

„Wann ist die nächste Sprechstunde?“ Betreuung und Beratung im Online Writing Lab - Ballweg, Sandra (Zeitschrift für Interkulturellen Fremdsprachenunterricht 13/11)

Schreiben lernen von Anfang an – Schreibförderung in Integrationskursen - Ballweg, Sandra (Deutsch als Zweitsprache 2)

DaF-Lehrende und das Europäische Sprachenportfolio - Stork, Antje; Ballweg, Sandra (InfoDaF4)

Regressionsanalyse - Kraft, Manfred; Lück, Sonja (Enzyklopädie der Wirtschaftsinformatik - Online-Lexikon)

Statistik - Kraft, Manfred; Lück, Sonja (Enzyklopädie der Wirtschaftsinformatik - Online-Lexikon)

Wilholt, Torsten, "Zahl und Wirklichkeit. Eine philosophische Untersuchung über die Anwendbarkeit der Mathematik", mentis Verlag: Paderborn 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hauser, Kai, “Gödel’s Program Revisited. I: The Turn to Phenomenology”, In: Bulletin of Symbolic Logic 12 (2006), 529–590 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lorenz, Kuno, “Logic as Tool of Science versus Logic as a Scientific Subject”, in: Johan van Benthem et al. (eds.), The Age of Alternative Logics. Assessing Philosophy of Logic and Mathematics Today. Based on the Conference on Philosophical Insights into Logic and Mathematics, Nancy, France, September 30–October 4, 2002, Dordrecht: Springer 2006, 299–310 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Vidal-Rosset, Joseph, “Does Gödel’s Incompleteness Theorem Prove that Truth Transcends Proof”, in: van Bentham et al. (eds.), The Age of Alternative Logics. Assessing Philosophy of Logic and Mathematics Today, Dordrecht: Springer 2006, 51–73 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)